Direct laser writing of sub-50 nm nanofluidic channels buried in glass for three-dimensional micro-nanofluidic integration - Liao, Yang; Cheng, Ya; Liu, Changning; Song, Jiangxin; He, Fei; Shen, Yinglong; Chen, Danping; Xu, Zhizhan; Fan, Zhichao; Wei, Xunbin; Sugioka, Koji; Midorikawa, Katsumi (Lab on a chip, 2013)
We report on the fabrication of nanofluidic channels directly buried in silicate glass with transverse widths down to less than 50 nm using three-dimensional (3D) femtosecond laser direct writing. Using this technique, integrated micro-nanofluidic systems have been produced by simultaneously writing micro- and nanofluidic channels arranged into various 3D configurations in glass substrates. The fabricated micro- and nanofluidic systems have been used to demonstrate DNA analysis, e.g. stretching of DNA molecules. Our technique offers new opportunities to develop novel 3D micro-nanofluidic systems for a variety of lab-on-a-chip applications.